Theoretical Justification of Plant Stems Vibro-Cutting in Dense Environment - Tarverdyan, A. P.; Khachatryan, A. Kh.; Altunyan, A. V. (ՀԱԱՀ հիմնադրամ)
The article considers the issue related to the disclosure of the reasons for the abrupt reduction of resistance force factors in case of plants stems vibro-cutting in dense medium through theory-based investigations. The computation scheme of the liquid motion in the vicinity of vibro-blade has been recommended, which enabled to derive differential equation of the motion resulted under the impact of interaction forces between the vibro-blade and environment. It has been proved, that the liquid in the vibro-blade vicinity is subjected to rapid damped oscillation, due to which the environmental resistance forces and the energy consumption rates are reduced in about 20 times against the same indices recorded in case of vibrationless cutting.
Keywords: Agricultural Engineering